Caffeine as a potential arousal enhancer: altered NMDA subunit gene expression without improving cognitive performance in REM sleep deprived rats - Sahin, Leyla; Cevik, Ozge Selin; Koyuncu, Dilan Deniz; Kocahan, Sayad (Cellular and Molecular Biology, 2019)
Caffeine is one of the most extensively consumed stimulants in the world and has been suggested to induce wakefulness by antagonizing the function of the adenosine A2A receptor. Therefore, we investigated the effects of chronic caffeine consumption on learning and memory in the REM sleep-deprived rats.Male Wistar rats (n = 50), were randomly assigned into 5 groups: Control (C), Caffeine (Cf), Pedestal Control (PC), Sleep Deprivation (SD), Sleep Deprivation and Caffeine (SD + Cf). Sleep deprivation procedure was applied as the flower-pot technique. SD and SD + Cf groups were deprived for 18 hours in a day for 21 days. Caffeine was administered daily in drinking water (0.3 gâ„L) for 5 weeks. For evaluated learning and memory function, Morris Water Maze Test (MWM) was used. Fluidigm Access Array was used for Grin2a, Grin2b, BDNF, cdk5/cdk5r1, CaMKIIa genes expression in the hippocampus. Distance moved and escape latency were decreased through trial days (p<0.05). However, there is no significant difference between groups for time spent in targeted quadrant during probe test for memory performance. Grin2a up-regulation was found in Cf and SD+Cf (p<0.05), and cdk5r1 increased in Cf and PC control (p<0.05). Also, BDNF up-regulation was found in PC group. Grin2b, Cdk5, CaMKIIa expression levels were not changed significantly. We showed chronic caffeine altered some of the hippocampal genes without changing learning and memory in REM sleep deprived rats. Chronic consumption of caffeine caused up-regulation in Grin2a that subunit of NMDA receptor. We supposed that chronic caffeine consumption maintained arousal without affecting learning and memory performance.